Symptom burden and relief in palliative care units of German Comprehensive Cancer Center and other hospitals - Berendt, Julia; Brunner, Sarah; Heckel, Maria; Tewes, Mitra; Ostgathe, Christoph; Gahr, Susanne (Journal of Cancer Research and Clinical Oncology, 2024)
Purpose: The National Hospice and Palliative Registry contains patient data from German hospice and palliative care facilities about symptoms. The aim of the study at hand is to differentiate symptom burden of patients in palliative care units between Comprehensive Cancer Center (CCC) and other hospitals regarding symptom burden and relief of patients in palliative care units. Methods: The registry analysis provided data of patients in palliative care units (2014–2018). We analyzed characteristic and symptom-related data on 18 symptoms, with considerable symptom-burdened patients (moderate or severe). We followed a cancer (yes/no) and facility-specific descriptive analysis (f, %, μ, Mdn, SD, V, r) using SPSS. Results: We evaluated 10,447 patient records (CCC: 4234 pts/non CCC 6,213 pts), 82% with a cancer diagnosis. For cancer patients, the mean age in CCC-affiliated palliative care units was 68 (SD 19–99) years, in others 73 (SD 23–104) years (p < 0.05; V = 0.2). The proportion of patients with significant symptom burden is lower in CCC-affiliated than in other palliative care units. The difference between facilities shows a significant weak effect in pain, vomiting and constipation, depressiveness, anxiety, and tension. The proportion of cases which symptom burden could be alleviated is higher in CCC-affiliated palliative care units with significant weak/medium effect in pain, nausea, vomiting, shortness of breath, constipation, wound care problems, depressiveness, anxiety, tension, confusion, and problems in organizing care. Conclusion: We found differences in symptom burden and symptom relief between CCC-affiliated and other palliative care units. CCCs should continue to feel responsible for sharing knowledge about symptom relief, such as through standard operating procedures and education.
CRIS-Team Scopus Importer:2024-04-05
Keywords: Cancer; Palliative care; Registry; Symptom burden; Symptom relief